Exploring the multiple land degradation pathways across the planet - Prăvălie, Remus (Earth-science reviews, 2021)
Land degradation has become one of the biggest environmental challenges human society is currently facing, which is why understanding the global pattern of this land crisis is absolutely necessary. However, so far, the multiple forms of this environmental issue have mainly been analysed in international scientific literature in a narrow traditional manner, frequently based on approaching a relatively low number of ordinary land degradation processes. Consequently, as this complex process has not been sufficiently well explored, this study aims to investigate global land degradation in an interdisciplinary and holistic manner, in terms of the multidimensional nature, causes, spatial footprint, multiple consequences (for the ecological and anthropogenic systems worldwide, but also for the global climate system) and various solutions to mitigate worldwide land multi-degradation. Based on various information investigated in more than 500 reliable scientific papers, the findings of this review paper showed that there currently are 17 land degradation pathways (aridity, biological invasions, coastal erosion, land erosion by water, land erosion by wind, land pollution, land subsidence, landslides, permafrost thawing, salinization, soil acidification, soil biodiversity loss, soil compaction, soil organic carbon loss, soil sealing, vegetation degradation and waterlogging), which are active on various spatial scales across the planet. Five of the seventeen land degradation dimensions were considered major land degradation pathways and explored in detail in this study (aridity, land erosion by water, salinization, soil organic carbon loss and vegetation degradation), considering several relevant criteria outlined in the paper (global spatial footprint, data availability, and impact on agricultural, ecological and climate systems). Essentially, it was found that the five global degradation processes significantly erode the multiple ecosystem functions and services of worldwide land systems, which are crucial for human wellbeing, life support and the Earth systems’ stability. Nonetheless, other land degradation processes can also be considered major land degradative pathways, although a main current impediment in their detailed investigation is the general lack of global data availability. Therefore, the study highlights the complexity and severity of global land degradation, and draws attention to the need for other studies to approach land degradation multidimensionally, which goes beyond the traditional perspectives focused on the conventional processes of water erosion, wind erosion or soil salinization. At the same time, the study highlights the fact that land degradation must be an urgent priority in governmental and international policies, which can rely on a wide range of control measures that are currently available (some of the relevant ones are explored in this paper) for combating this disrupting environmental process rapidly, efficiently and on a large scale throughout the world.